2007
DOI: 10.1111/j.1460-9568.2007.05802.x
|View full text |Cite
|
Sign up to set email alerts
|

Small‐conductance Cl channels contribute to volume regulation and phagocytosis in microglia

Abstract: The shape and volume of microglia (brain immune cells) change when they activate during brain inflammation and become migratory and phagocytic. Swollen rat microglia express a large Cl(-) current (I(Clswell)), whose biophysical properties and functional roles are poorly understood and whose molecular identity is unknown. We constructed a fingerprint of useful biophysical properties for comparison with I(Clswell) in other cell types and with cloned Cl(-) channels. The microglial I(Clswell) was rapidly activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 62 publications
5
68
0
Order By: Relevance
“…Phagocytic microglia are rod-shaped or nearly spherical. 28 The relative order of mRNA expression for the Na + /Ca 2+ exchangers was: NCX1 > NCX3 > NCX2, where '>' denotes a significant difference from the preceding gene (p < 0.05). No significant changes were detected following a 1 h treatment with opsonized zymosan to stimulate phagocytosis and the respiratory Role of Reversed Na + /Ca 2+ Exchange in Microglia burst (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phagocytic microglia are rod-shaped or nearly spherical. 28 The relative order of mRNA expression for the Na + /Ca 2+ exchangers was: NCX1 > NCX3 > NCX2, where '>' denotes a significant difference from the preceding gene (p < 0.05). No significant changes were detected following a 1 h treatment with opsonized zymosan to stimulate phagocytosis and the respiratory Role of Reversed Na + /Ca 2+ Exchange in Microglia burst (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such a mechanism is consistent with the dramatically reduced respiratory burst when voltage-dependent (K v ) or Ca 2+ -dependent (SK) channels are blocked in microglia. 22,24,68 In addition, Cl -influx through anion channels 28,69 could help counteract the depolarization resulting from electron efflux. We recently showed that anion channels are major determinants of the membrane potential in microglia 26 and thus, should affect Ca 2+ entry, and also contribute to phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phagocytosis in human macrophages is accompanied by changes in ion channel currents (24), and Cl Ϫ channels are important for phagocytosis in neutrophil and microglia (15,37). Propofol, also known as a GABA A receptor agonist, binds to the ␤ 2 -subunit of the GABA A receptor (4), which regulates Cl Ϫ channels (32).…”
Section: Discussionmentioning
confidence: 99%
“…Propofol binds to the ␤ 2 -subunit of the GABA A receptor (4,16), which regulates Cl Ϫ channels (32). Some investigators have reported that ion channels, such as those regulating Cl Ϫ and Ca 2ϩ fluxes, might affect phagocytosis by macrophages and microglia (15,24). The effects of propofol on macrophage phagocytic activity, therefore, may be potentially important in surgical wound healing.…”
mentioning
confidence: 99%